Calcium sulphosilicate mineral clinker with high carbonization activity, raw material and preparation method and hardening method of calcium sulphosilicate mineral clinker
By introducing lithium, potassium, sodium or strontium into calcium sulfosilicate, its carbonization reaction activity is improved and its maintenance is maintained in a carbon dioxide environment, the problems of high carbon emissions and manufacturing costs in the cement industry are solved, and high-intensity carbonization hardening is achieved and low carbon emission effects.
Patent Information
- Application Number
- CN202411752707.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The cement industry emits a large amount of carbon dioxide during the calcination process, and the prior art avoids the formation of calcium sulfosilicate mineral phase, resulting in high carbon emissions and manufacturing costs.
Using high carbonization activity of calcium sulfosilicate mineral clinker, the carbonization reaction activity is improved by introducing lithium, potassium, sodium or strontium into calcium sulfosilicate, and the carbonization reaction activity is improved by curing in a carbon dioxide environment to achieve high Carbon hardening of strength.
Significantly reduce carbon emissions, improve mechanical properties, absorb carbon dioxide through carbonization reaction, reduce carbon emissions during clinker firing, and increase carbon sequestration.
Smart Images

Figure CN119191736A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement clinker preparation, and in particular to a calcium sulfosilicate mineral clinker with high carbonization activity, a raw material and a preparation method and a hardening method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the acceleration of economic development and industrialization, greenhouse gas emissions continue to rise, bringing about a series of environmental problems such as rising global temperatures and frequent extreme weather. As carbon dioxide emissions from the cement industry account for nearly 15% of China's total industrial emissions, the cement industry is actively exploring green and low-carbon development paths, by improving energy efficiency, promoting new materials, and implementing carbon capture and storage technology, in order to reduce the carbon footprint of cement products and promote the sustainable development of the cement industry.
[0004] During the calcination process of ordinary Portland cement clinker, a large amount of carbon dioxide is released due to the decomposition of limestone and the combustion of fuel. The calcination temperature of calcium sulfosilicate is below 1200℃, and the energy consumption is relatively low. Lower energy consumption means lower carbon emissions. In addition, part of the calcium oxide required for the formation of calcium sulfosilicate can be provided by waste gypsum, and the calcium, silicon and calcium sulfate raw materials required for the formation of calcium sulfosilicate mineral phase are widely available, which helps to reduce manufacturing costs. However, calcium sulfosilicate is generally considered to be an inert mineral, so the formation of calcium sulfosilicate mineral phase is avoided as much as possible during the production of cement clinker. Summary of the invention
[0005] The present invention provides a calcium sulfosilicate mineral clinker with high carbonization activity, a raw material, and a preparation method and a hardening method thereof, which have excellent carbonization activity, so that they can react with carbon dioxide to obtain high strength, not only achieving high carbon fixation and reducing carbon emissions, but also having excellent mechanical properties. Specifically, the technical solution of the present invention is as follows.
[0006] In the first aspect, the present invention discloses a calcium sulfosilicate mineral clinker with high carbonization activity, which comprises the following mineral phases by mass percentage: 87.2-95.1% calcium sulfosilicate (C5S2$), 2.6-9.5% dicalcium silicate (C2S), and the remainder comprises unreacted raw materials, unavoidable impurities, etc. Wherein: part of the calcium element in the crystal lattice of the calcium sulfosilicate is replaced by at least one of lithium element (Li), sodium element (Na), potassium element (K), and strontium element (Sr). The lithium element accounts for 0.25-0.9% of the mass of the calcium sulfosilicate, the sodium element accounts for 0.15-0.7% of the mass of the calcium sulfosilicate, the potassium element accounts for 0.05-0.65% of the mass of the calcium sulfosilicate, and the strontium element accounts for 0.4-1.0% of the mass of the calcium sulfosilicate.
[0007] In a second aspect, the present invention discloses a raw material for preparing calcium sulfosilicate mineral with high carbonization activity, comprising the following raw materials: a calcium raw material, a silicon raw material, a gypsum raw material and a modifier. Wherein: the mass ratio of the calcium raw material, the silicon raw material and the gypsum raw material is 8.4:2.6:3.6~8.4:2.6:4. The amount of the modifier added is 0.1~1% of the total mass of the raw materials. The modifier includes at least one of lithium carbonate, sodium carbonate, potassium carbonate, strontium carbonate, strontium oxide, strontium slag, etc.
[0008] Furthermore, the calcium raw material includes at least one of calcium carbonate, high-calcium fly ash, carbide slag, limestone and the like.
[0009] Furthermore, the siliceous raw material includes at least one of silicon dioxide, sandstone, silica fume, quartz sand, coal gangue, etc.
[0010] Furthermore, the gypsum raw material includes at least one of dihydrate gypsum, desulfurized gypsum, fluorite, phosphogypsum, anhydrite and the like.
[0011] In a third aspect, the present invention discloses a method for preparing the calcium sulfosilicate mineral clinker with high carbonization activity, comprising the following steps: uniformly mixing the calcium raw material, the silicon raw material, the gypsum raw material and the modifier and then calcining the mixture. After the mixture is calcined, the calcined product is rapidly cooled to obtain the mixture.
[0012] Furthermore, the fineness of the calcium raw material, the silicon raw material, the gypsum raw material and the modifier is not less than 200 meshes.
[0013] Furthermore, the calcination temperature is 1100-1200° C., and the calcination time is 3-6 hours.
[0014] In a fourth aspect, the present invention discloses a method for hardening the calcium sulfosilicate mineral clinker with high carbonization activity, comprising the following steps: mixing the calcium sulfosilicate mineral clinker with water and placing it in a carbon dioxide environment for curing, and obtaining a calcium sulfosilicate mineral hardened body after completion.
[0015] Furthermore, the mass ratio of the calcium sulfosilicate mineral clinker to water is 1:0.1-0.2.
[0016] Furthermore, the carbon dioxide pressure in the curing environment is 0.1-0.4 MPa, and the curing time is 1-24 hours.
[0017] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects: After the calcium sulfosilicate in the mineral clinker of the present invention is modified by a modifier, it not only has excellent carbonization reaction activity, but also has a larger carbon fixation amount, and can use carbon dioxide to obtain ultra-high mechanical strength. This is because the lithium, potassium, sodium or strontium ions provided by the modifier can be dissolved in the crystal lattice of calcium sulfosilicate at high temperature and replace part of the calcium element therein, thereby changing the total state density of the calcium sulfosilicate unit cell. At the same time, the doped elements introduce impurity energy levels to the right of the Fermi level (i.e., the bottom of the conduction band), change the active sites of the crystal nucleophilic reaction, increase the effective charge of the calcium element, enhance the reaction activity of the crystal, and thus promote the dissolution ability of the calcium source. Since the early stage of the carbonization reaction is mainly a crystal dissolution reaction dominated by the dissolution of the calcium element, the calcium sulfosilicate of the present invention has excellent carbonization hardening ability, so that the clinker obtains excellent mechanical properties. Moreover, since carbon dioxide can be absorbed during the carbonization process, the carbon emissions generated during the clinker firing process can be offset / reduced to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 This is a sample of calcium sulfosilicate mineral clinker with high carbonization activity prepared in Example 1 below.
[0020] Figure 2 The XRD pattern of the calcium sulfosilicate mineral clinker prepared in Example 1 below.
[0021] Figure 3 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in the following Example 2.
[0022] Figure 4 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in Example 3 below.
[0023] Figure 5 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in Example 4 below.
[0024] Figure 6This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in Example 5 below.
[0025] Figure 7 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in the following Example 6.
[0026] Figure 8 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in the following Example 7.
[0027] Fig. 9 This is the XRD pattern of the calcium sulfosilicate mineral clinker prepared in the following Example 8. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0029] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.
[0030] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.
[0031] In the following examples, the calcium carbonate, silicon dioxide, dihydrate gypsum, potassium carbonate, sodium carbonate, lithium carbonate, strontium carbonate, and strontium oxide are from Sinopharm Chemical Reagent Co., Ltd. The limestone, silica fume, desulfurized gypsum, fluorite, phosphogypsum, high-calcium fly ash, and coal gangue are from Shandong Shanlu Environmental New Materials Co., Ltd., carbide slag is from Hengwang Environmental Engineering Co., Ltd., and lithium slag is from Jiangxi Yichun Yinli New Energy Co., Ltd.
[0032] Example 1 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, calcium carbonate, silica fume, and dihydrate gypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of calcium carbonate: silica fume: dihydrate gypsum = 8.4:2.6:3.6, and lithium carbonate is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of lithium carbonate is 0.5%.
[0033] (2) Add water to the raw material powder and mix well, then press into raw material cake, heat to 1150°C at a heating rate of 10°C / min and keep warm for 5 hours. After completion, the calcined product is air-cooled to room temperature and crushed (such as Figure 1 The mixture is ground and sieved to obtain 200-mesh clinker powder.
[0034] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 2 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 93.8wt.%, dicalcium silicate (C2S) 3.4wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0035] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.12 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.2 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0036] Example 2 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, limestone, silicon dioxide, and desulfurized gypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of limestone, silicon dioxide, and desulfurized gypsum = 8.4:2.6:3.7, and sodium carbonate is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of the sodium carbonate is 0.1%.
[0037] (2) adding water to the raw material powder and mixing evenly, and then pressing into raw material cakes, heating the raw material cakes to 1100° C. at a heating rate of 10° C. / min and keeping the temperature for 3 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 200-mesh clinker powder.
[0038] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 3 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 87.2wt.%, dicalcium silicate (C2S) 9.5wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0039] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.12 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.2 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0040] Example 3 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, carbide slag, quartz sand, and fluorgypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of carbide slag, quartz sand, and fluorgypsum = 8.4:2.6:4, and potassium carbonate is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of potassium carbonate is 0.8%.
[0041] (2) adding water to the raw material powder and mixing evenly, and then pressing into raw material cakes, heating the raw material cakes to 1200° C. at a heating rate of 10° C. / min and keeping the temperature for 4 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 300-mesh clinker powder.
[0042] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 4 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 91.7wt.%, dicalcium silicate (C2S) 6.9wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0043] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.1 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.4 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0044] Example 4 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, high calcium fly ash, coal gangue, and desulfurized gypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of high calcium fly ash, coal gangue, and phosphogypsum = 8.4:2.6:3.8, and lithium carbonate and potassium carbonate are added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of lithium carbonate is 0.7% and the mass proportion of potassium carbonate is 0.3%.
[0045] (2) adding water to the raw material powder and mixing evenly, and then pressing into raw material cakes, heating the raw material cakes to 1175°C at a heating rate of 10°C / min and keeping the temperature for 6 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 400-mesh clinker powder.
[0046] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 5 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 92.5wt.%, dicalcium silicate (C2S) 4.7wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0047] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.2 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.1 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0048] Example 5 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, calcium carbonate, silica fume, and dihydrate gypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of calcium carbonate: silica fume: dihydrate gypsum = 8.4:2.6:3.6, and strontium carbonate is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of strontium carbonate is 0.5%.
[0049] (2) adding water to the raw material powder, mixing evenly, and pressing into raw material cakes, heating the raw material cakes to 1150° C. at a heating rate of 10° C. / min and keeping the temperature for 5 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 200-mesh clinker powder.
[0050] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 6 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 95.1wt.%, dicalcium silicate (C2S) 2.6wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0051] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.12 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.2 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0052] Example 6 A method for preparing calcium sulfosilicate mineral clinker with high carbonization activity comprises the following steps: (1) First, limestone, silicon dioxide, and desulfurized gypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of limestone, silicon dioxide, and desulfurized gypsum = 8.4:2.6:3.7, and strontium oxide is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of strontium oxide is 0.1%.
[0053] (2) adding water to the raw material powder and mixing evenly, and then pressing into raw material cakes, heating the raw material cakes to 1100° C. at a heating rate of 10° C. / min and keeping the temperature for 3 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 200-mesh clinker powder.
[0054] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 7 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 89.5wt.%, dicalcium silicate (C2S) 8.1wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0055] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.12 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.2 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0056] Example 7 A method for preparing calcium sulfosilicate mineral clinker comprises the following steps: (1) First, grind calcium carbonate, silica fume and dihydrate gypsum separately, and then sieve to obtain raw material powder of 200 mesh. Then, mix the raw materials evenly according to the mass ratio of calcium carbonate: silica fume: dihydrate gypsum = 8.4:2.6:3.6 to obtain raw material powder.
[0057] (2) adding water to the raw material powder, mixing evenly, and pressing into raw material cakes, heating the raw material cakes to 1150° C. at a heating rate of 10° C. / min and keeping the temperature for 5 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 200-mesh clinker powder.
[0058] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Figure 8 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 92.9wt.%, dicalcium silicate (C2S) 4.2wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0059] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.12 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.2 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0060] Example 8 A method for preparing calcium sulfosilicate mineral clinker comprises the following steps: (1) First, carbide slag, quartz sand, and fluorgypsum are ground separately, and then sieved to obtain raw material powder of 200 mesh. Then, the raw materials are mixed according to the mass ratio of carbide slag, quartz sand, and fluorgypsum = 8.4:2.6:4, and lithium slag is added thereto and mixed evenly to obtain raw material powder, wherein the mass proportion of the lithium slag is 0.8%.
[0061] (2) adding water to the raw material powder and mixing evenly, and then pressing into raw material cakes, heating the raw material cakes to 1200° C. at a heating rate of 10° C. / min and keeping the temperature for 4 hours. After completion, the calcined product is air-cooled to room temperature, crushed, ground, and sieved to obtain 300-mesh clinker powder.
[0062] The clinker powder prepared in this example was subjected to XRD test (the results are shown in FIG. Fig. 9 The results show that the cement clinker includes: calcium sulfosilicate (C5S2$) 85.4wt.%, dicalcium silicate (C2S) 10.5wt.%, and the rest includes unreacted raw materials, unavoidable impurities, etc.
[0063] The clinker powder prepared in this embodiment is mixed with water in a mass ratio of 1:0.1 and stirred evenly, and then pressed into a test block of length × width × height = 20 × 20 × 20 mm at a pressure of 15 MPa. The test block is then placed in a closed carbonization box (carbon dioxide accounts for 99% by volume) for carbonization curing. The gas pressure is set to 0.4 MPa. After curing for 1h, 2h, 18h and 24h, the CO2 ignition loss is tested by thermogravimetry (TG), and the carbon fixation amount of the test block is calculated. In addition, the compressive strength of the test block after carbonization curing for 24h is tested, and the results are shown in the following table: .
[0064] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A calcium sulfosilicate mineral clinker with high carbonization activity, characterized in that: In terms of mass percentage, the clinker includes the following mineral phases: 87.2-95.1% of calcium thiosilicate, 2.6-9.5% of dicalcium silicate, and the remainder includes unreacted raw materials and inevitable impurities; wherein: part of the calcium element in the crystal lattice of the calcium thiosilicate is replaced by at least one of lithium, sodium, potassium and strontium; the lithium element accounts for 0.25-0.9% of the mass of the calcium thiosilicate, the sodium element accounts for 0.15-0.7% of the mass of the calcium thiosilicate, the potassium element accounts for 0.05-0.65% of the mass of the calcium thiosilicate, and the strontium element accounts for 0.4-1.0% of the mass of the calcium thiosilicate.
2. A raw material for preparing calcium sulfosilicate mineral with high carbonization activity, characterized in that: The invention comprises the following raw materials: a calcium raw material, a silicon raw material, a gypsum raw material and a modifier; wherein: the mass ratio of the calcium raw material, the silicon raw material and the gypsum raw material is 8.4:2.6:3.6~8.4:2.6:4; the addition amount of the modifier is 0.1~1% of the total mass of the raw materials; the modifier comprises at least one of lithium carbonate, sodium carbonate, potassium carbonate, strontium carbonate, strontium oxide and strontium slag.
3. The raw material for preparing calcium sulfosilicate mineral with high carbonization activity according to claim 2, characterized in that: The calcium raw material includes at least one of calcium carbonate, high-calcium fly ash, carbide slag and limestone.
4. The raw material for preparing calcium sulfosilicate mineral with high carbonization activity according to claim 2, characterized in that: The siliceous raw material includes at least one of silicon dioxide, sandstone, silica fume, quartz sand and coal gangue.
5. The raw material for preparing calcium sulfosilicate mineral with high carbonization activity according to any one of claims 2 to 4, characterized in that: The gypsum raw material includes at least one of dihydrate gypsum, desulfurized gypsum, fluorite, phosphogypsum and anhydrite.
6. A method for preparing the calcium sulfosilicate mineral clinker with high carbonization activity, characterized in that: The method comprises the following steps: uniformly mixing the calcium raw material, silicon raw material, gypsum raw material and modifier in the raw material according to any one of claims 2 to 5 and then calcining the mixture; and rapidly cooling the calcined product to obtain the mixture.
7. The method for preparing calcium sulfosilicate mineral clinker with high carbonization activity according to claim 6, characterized in that: The calcination temperature is 1100-1200°C and the time is 3-6 hours; Alternatively, the fineness of the calcium raw material, the silicon raw material, the gypsum raw material and the modifier is not less than 200 meshes.
8. A method for hardening the calcium sulfosilicate mineral clinker with high carbonization activity according to claim 1, or the calcium sulfosilicate mineral clinker with high carbonization activity obtained by the preparation method according to claim 6 or 7, characterized in that: The method comprises the following steps: mixing the calcium sulfosilicate mineral clinker with water and placing the mixture in a carbon dioxide environment for curing, and obtaining a calcium sulfosilicate mineral hardened body after curing.
9. The hardening method of calcium sulfosilicate mineral clinker with high carbonization activity according to claim 8, characterized in that: The mass ratio of the calcium sulfosilicate mineral clinker to water is 1:0.1-0.
2.
10. The hardening method of calcium sulfosilicate mineral clinker with high carbonization activity according to claim 8 or 9, characterized in that: The carbon dioxide pressure in the curing environment is 0.1-0.4 MPa; or, the curing time is 1-24 hours.
Citation Information
Patent Citations
Calcium sulphosilicate-based cementing material
CN117303763A
Carbonation hardened low-calcium cement and preparation and hardening method thereof
CN117645420A
Monocalcium silicate-calcium sulphosilicate-dicalcium silicate cement clinker, cement composition and preparation method of cement composition
CN118479760A
Cited By
High-carbonization-resistance super-sulfate cement material as well as preparation method and application thereof
CN122102635A
A high-carbonization-resistance type ultra-sulfate cement material, a preparation method and application thereof
CN122102635B
Early-strength belite sulphoaluminate cement clinker and preparation method thereof
CN122212516A
Early-strength belite sulphoaluminate cement clinker and preparation method thereof
CN122212516B